Genetic evidence suggests that depression increases the risk of erectile dysfunction: A Mendelian randomization study - Ma, Kai; Song, Pan; Liu, Zhenghuan; Yang, Luchen; Wang, Linchun; Zhou, Jing; Chen, Junhao; Dong, Qiang (Frontiers in Genetics, 2022)
Abstract Background The causal relationship between depression and erectile dysfunction (ED) is still uncertain. Objectives To identify the genetically predicted causality of depression on ED through Mendelian randomization (MR). Materials and methods A comprehensive GWAS meta-analysis comprising 807,553 people of Europeans provided single nucleotide polymorphisms (SNPs) information for depression, and another genome-wide association analysis involving 223,805 European ancestries measured SNPs for ED. The inverse variance weighted (IVW) method was used as the primary MR analysis method to evaluate causal effects. In addition, the maximum likelihood method, MR-egger, weighted median, robust adjusted contour score (MR.RAPS), and MR pleiotropic residual and outlier (MR-PRESSO) methods were used as supplements for sensitivity analysis. Results According to the IVW analysis, depression significantly increases the incidence of ED (Odds ratio [OR] = 1.68, 95 percent confidence interval [CI] = 1.38 - 2.05, P<0.001). In sensitivity analyses, the ORs for the maximum likelihood method, MR-Egger, weighted median, MR.RAPS, and MR-PRESSO are 1.70 (95% CI = 1.39 – 2.08, P < 0 .001), 1.94 (95% CI = 0.63 – 6.01, P > 0 .05), 1.59 (95% CI = 1.21 – 2.10, P < 0 .001), 1 .70 (95% CI = 1.39 –2.08, P < 0 .001), and 1.68 (95% CI = 1.40 – 2.04, P < 0 .001). There is no clear indication of potential heterogeneity or pleiotropy (P for MR-Egger intercept = -0.0038; P for global test = 0.594; P for Cochran's Q statistics > 0.05). Conclusion Genetically predicted depression plays a potentially causal role in the occurrence of ED.